Chemical stabilization of calcareous sand by polyurethane foam adhesive. (9th August 2021) - Tao, Gaoliang; Yuan, Jinghan; Chen, Qingsheng; Peng, Wan; Yu, Ronghu; Basack, Sudip
Highlights: Strength and stiffness of calcareous sand is enhanced by using PFA for chemical stabilization. The influence of PFA on calcareous sand characteristics are different for varying particle gradation. The shear strength as well as CBR of calcareous sand is greatly improved when stabilized by PFA. The test results are useful in determining the optimum content of PFA to be used in a particular calcareous sand with specific particle gradation. Abstract: The calcareous sand existing at the South China sea is characterized by low shear strength with high compressibility. Associated with particle breakage, foundations built on such problematic soil initiates undrained failure with uneven foundation settlement, unless adequate ground improvement technique is adopted. In this paper, chemical soil stabilization is carried out by applying Polyurethane Foam Adhesive (PFA) to the virgin soil. Improvement of strength and stiffness of the treated soil have been investigated in detail by a series of triaxial consolidation and drainage tests followed by California bearing ratio tests. The effect of particle gradation on the stress–strain curve and CBR values of the stabilized calcareous sand as well as the influence on peak shear stress and shear strength index has been studied. The test results show that the PFA is effective in improving the mechanical properties of calcareous sand. The particle gradation has significant effects on the stress–strain response of the stabilized calcareous sand under different PFA contents. Optimal PFA content for each grading of calcareous sand was proposed. The test results of this work would be beneficial for engineering practice in dealing with the bearing capacity and settlement of foundations involving calcareous sand.